PENGARUH KULIAH KERJA PROFESI TERHADAP TINGKAT PENGETAHUAN MAHASISWA TENTANG MANAJEMEN PERKEBUNAN KELAPA SAWIT - Wibowo, Arif Ravi; Sibarani, Ebenezer Muaratama; Kusnendi, Faizal Shofwan; Putri, Halida Adistya; Madusari, Sylvia; Handini, Aline Sisi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
In vocational education, field practice is not only considered as a complement, but also as the core of learning that can produce graduates who are ready to contribute directly to the world of work. Professional Job Lecture (PJL) is a mandatory courses in the sixth semester. All learning is carried out practically. This research aims to examine the level of knowledge of students who are participants in the PJL. The research was conducted on 15 August until 31 October 2023 at the Citra Widya Edukasi Oil Palm Polytechnic on all students of the Production Technology of Plantation Crops study program for the year entering 2021. The number of students in the survey was 37 people. The student has participated in PJL activities at the Subang oil palm educational plantation of the Citra Widya Edukasi Oil Palm Polytechnic for 20 days. Primary data was used in this research through filling out questionnaires. Level of confidence and knowledge of students measured by submitting statements and questions in online questionnaire. Questionnaire-filling was carried out on the first day of the PJL and 2 months after the activity was completed. The level of knowledge of students PJL about oil palm plantation management was medium to very high level based on hypothetical data categorization. The majority of students have a high level of knowledge as much as 62.86%. Effective communication based on SKKN topic for Plantation Asisstants was the highest percentage of corecct answers namely 89.86. Self-confidence was increased after PJL with the number of students by 31 people.